2022
DOI: 10.1097/olq.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

Reported Neurologic, Ocular, and Otic Manifestations Among Syphilis Cases—16 States, 2019

Abstract: Neurologic, ocular, and otic manifestations were infrequently reported overall, but prevalence increased with age and was higher among human immunodeficiency virus–infected persons reporting injection drug use and staged as unknown duration/late syphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Neurosyphilis and its subtypes of ocular syphilis and otosyphilis are rare among patients with syphilis, though true prevalence may be underestimated due to under-reporting. A 2019 analysis of syphilis cases from 16 states found that ocular syphilis made up around 1% of cases, while otosyphilis made up 0.4% of cases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurosyphilis and its subtypes of ocular syphilis and otosyphilis are rare among patients with syphilis, though true prevalence may be underestimated due to under-reporting. A 2019 analysis of syphilis cases from 16 states found that ocular syphilis made up around 1% of cases, while otosyphilis made up 0.4% of cases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otosyphilis typically presents with hearing loss, tinnitus, and vertigo [ 5 ]. Both ocular and otologic forms of neurosyphilis are rare manifestations of syphilis, together encompassing less than 2% of reported cases [ 6 ]. Here, we present a particularly unusual case of concurrent ocular and otologic neurosyphilis in an immunocompetent young adult.…”
Section: Introductionmentioning
confidence: 99%
“…This ocular syphilis cluster is the first documented with epidemiologic linkage among cases attributable to heterosexual transmission. In 2019, a study of 41,187 syphilis cases from 16 jurisdictions with complete reporting, including Michigan, found that incidence of systemic manifestations were rare (neurosyphilis, 1.1%; ocular syphilis, 1.1%; and otosyphilis, 0.4%) ( 1 ). A cluster of ocular syphilis was reported in Seattle in 2015 among four men who have sex with men, three of whom were HIV-positive and two of whom were sex partners ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ocular and neurosyphilis can occur at any stage of syphilis, a 2019 U.S. prevalence estimate found that these clinical manifestations occurred more commonly during late-stage syphilis, and were most prevalent among persons aged ≥65 years and those reporting injection drug use ( 1 ). In contrast, among cases in the current reported cluster, all patients had early-stage disease, and were aged 40–60 years, and none reported injection drug use or transactional sex.…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection, syphilis can invade the nervous system and result in a wide array of nonspecific symptoms, contributing to a strong potential for misdiagnosis. [ 3 ] Otosyphilis is a form of audiovestibular dysfunction due to syphilis, [ 4 ] and this condition is very rare. Prior reports pertaining to otosyphilis have primarily focused on hearing impairment, with peripheral vestibulopathy having only been reported only in a few cases.…”
Section: Introductionmentioning
confidence: 99%